Contibutuins of Muslims to Fundamental Research - Hafiz Salmanul Farizy (Penerbit Hellow Pustaka, 2024)
The period spanning from the eighth to the thirteenth centuries, often referred to as the Islamic Golden Age, was marked by significant advancements in human knowledge attributed to Muslim scholars. The influence of this era is still evident today through various aspects of our daily lives, including the numeral system we use, terms such as algebra, algorithm, and almanac, as well as the nomenclature of celestial bodies. Unfortunately, much of this historical significance remains overlooked, as contemporary views of the Islamic world have largely diminished appreciation for its rich intellectual heritage. In contrast, this article aims to present an alternative viewpoint that diverges from the narratives commonly portrayed in 24-hour news cycles and online platforms. It is crucial to acknowledge the enduring legacy of Muslim contributions to intellectual progress, which have been recognized within Western society.